The Influences of Travel Expenses on the Indicator Factors of Sustainability in GMS Member Countries - SIHABUTR, Chaturaporn; NONTHAPOT, Sakkarin (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021, 2021)
The Greater Mekong Subregion (GMS) member countries contain tourism resources that can attract foreign tourists to visit. This is also a good opportunity for national development under the concept of sustainability in three dimensions, i.e., environmental, economic, and social. Data from 1990 to 2019 was used, which were brought for the unit root test. Autoregressive distributed lag (ARDL) was used for finding the cointegration, and the vector error correction model (VECM) and Vector autoregression (VAR) were utilized for finding the short-term relationship. The Granger causality test was based on the travel expenses on the factors of sustainability. The results revealed that the data had different stationarity levels. Similarly, the influences of travel expenses on the dimensions of sustainability of each country were different, too. The long-term relationship was found from the travel expenses on the environmental dimension in Cambodia, Myanmar, and Thailand. The travel expenses were the Granger causality for the environmental dimension in those countries, and had a long-term relationship on the social dimension in Cambodia, Laos, Myanmar, and Thailand. However, this factor only showed the Granger causality on the social dimension in Myanmar. For the economic dimension, travel expenses had a long-term relationship only in Cambodia, and the Granger causality for the economic dimension in Cambodia and Thailand. However, travel expenses did not affect the sustainability in any dimensions in Vietnam, which possibly implied that the influences of travel expenses on sustainability in different indicators depended on the structure, readiness, and the context of each country.